Karakteristik Penataan Ruang Perpustakaan Sekolah SMPN 1 Lubuk Sikaping - Rahmat Syauqi Deswin; Nurizzati Nurizzati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This type of research is qualitative research using descriptive methods. The data source in this research is the Head of the Library at SMPN 1 Lubuk Suhuing. The data for this research are the results of interviews with the head of the library at SMPN 1 Lubuk Suhuing. The instrument for this research was the researcher himself using an interview guide, notebook, digital camera and recording device. The data collection technique is carried out in five stages, namely: (1) this observation technique is based on direct experience (2) the observation technique allows you to see and observe yourself, then record behavior and events as they actually occur. (3) observation allows researchers to record events in situations related to proportional knowledge or knowledge directly obtained from data. (4) observation techniques enable researchers to understand complex situations. (5) in certain cases where interview techniques are not possible to carry out, observation becomes a tool. Based on the research results, it was found that: The research results of the library space arrangement according to Lasa HS (2007) amounted to 7 points, 3 points were appropriate while 4 points were not appropriate, thus the research results found that the characteristics of the library room arrangement at SMPN 1 Lubuk Suhuing could it is said to be not fully appropriate or in other words does not meet the spatial planning standards according to Lasa HS (2007).